Implementing the Precautionary Principle through Stakeholder Engagement for Product and Service Development - Cucuzella, Carmela; De Coninck, Pierre (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2007)
The precautionary principle is a sustainable development principle that attempts to articulate an ethic in decision making since it deals with the notion of uncertainty of harm. Uncertainty becomes a weakness when it has to serve as a predictor by which to take action. Since humans are responsible for their actions, and ethics is based in action, then decisions based in uncertainty require an ethical framework. Beyond the professional deontological responsibility, there is a need to consider the process of conception based on an ethic of the future and therefore to develop a new ethical framework which is more global and fundamental. This will expose the justifications for choices, present these in debates with other stakeholders, and ultimately adopt an axiology of decision making for conception.Responsibility and participative discourse for an equal justice among actors are a basis of such an ethic. By understanding the ethical framework of this principle and applying this knowledge towards design or innovation, the precautionary principle becomes operational. This paper suggests that to move towards sustainability, stakeholders must adopt decision making processes that are precautionary. A commitment to precaution encourages a global perspective and the search for alternatives. Methods such as alternative assessment and precautionary deliberation through stakeholder engagement can assist in this shift towards sustainability.